Effectiveness of Bradyrhizobium isolates on seedling growth and nitrogen content in soybean [Glycine max (L.) Merrill] - Pant, Bikram D; Prasad, Braj N (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.1-3